2008
DOI: 10.1007/s12032-008-9061-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukemia following the treatment of rectal adenocarcinoma

Abstract: Solid tumors may occur in 3% of the patients with chronic myeloid leukemia (CML). Philadelphia (Ph)-positive CML was diagnosed in a 66-year-old man upon a white blood cell count of 58.1 x 10(9)/L. He had no symptoms and physical findings 3 years after treatment for rectal adenocarcinoma. Imatinib mesylate 400 mg/day was started and white blood cell count was lowered to 5.7 x 10(9)/L in 1 month. The patient had received several chemotherapeutic agents such as 5-fluorouracil, irinotecan, raltitrexed, capecitabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Our case was treated with bevacizumab because KRAS mutation. A study (Kadikoylu et al, 2008), reported that 5-flurouracil, oxaliplatin, irinotecan, each of them can be carcinogenic and also in other case report (Vakili-Sadeghi and Omranpour, 2013) the case received these drugs during colon cancer that developed CML. In this study, the patient for colon cancer was treated with capecitabine, oxaliplatin and irinotecan.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Our case was treated with bevacizumab because KRAS mutation. A study (Kadikoylu et al, 2008), reported that 5-flurouracil, oxaliplatin, irinotecan, each of them can be carcinogenic and also in other case report (Vakili-Sadeghi and Omranpour, 2013) the case received these drugs during colon cancer that developed CML. In this study, the patient for colon cancer was treated with capecitabine, oxaliplatin and irinotecan.…”
Section: Discussionmentioning
confidence: 89%
“…Although CML accounts for a small percentage of secondary leukemia, reports on treatment-related CML are increasing and several cases of CML in patients treated for thyroid cancers, esophageal, gastric, lung, cervical, malignant fibrous histiocytoma and breast cancers have been reported (Vakili-Sadeghi and Omranpour, 2013). Cancer treatment modalities, including radiotherapy and chemotherapy, could themselves increase the risk of developing secondary malignancies (Kadikoylu et al, 2008). NRAS/BRAF mutation probably is effective in treatment of colorectal cancer patients with KRAS wild-type and in patients with KRAS wild-type should be specified NRAS/BRAF testing to determine which patients will benefit from anti-EGFR therapy (Payandeh et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Çoğunlukla tedavi ilişkili miyeloid neoplaziler gözlenmesine rağmen ALL vakaları da gözlenmektedir. 8,11 Ishizawa ve ark., tedavi ilişkili lösemilerde %12'sinin ALL vakaları olduğunu rapor etmişlerdir.…”
Section: Discussionunclassified
“…These clinical manifestations have featured both types of t-MN. The clinical characteristics of 8 patients who developed TRL after treatment with OXP are summarized in table 1 [7, 8, 9, 10, 11, 12, 13]. There were 5 male and 3 female patients with a mean age of 64 years (range, 25–79).…”
Section: Discussionmentioning
confidence: 99%